2006
DOI: 10.2147/tcrm.2006.2.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of introducing anticoagulation-related prescribing guidelines in a hospital setting using academic detailing

Abstract: Aim: Assess the impact of using academic detailing-assisted guideline roll-out on warfarin initiation, reversal of warfarin overanticoagulation, and uptake of deep vein thrombosis (DVT) prophylaxis across 4 metropolitan teaching hospitals. Methods: Baseline data were collected for 3 months prior to intervention. Prescribers were then informed about the guidelines, including feedback of current hospital performance and the basis for the guidelines. Post-intervention data were collected for 3 months after guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…During the first week of warfarin initiation, the percentage of INRs of more than 4 were reported as 7% by Roberts et al. (10) and up to 32% by Roberts and Adams (11). The baseline cohort of this study at 27% could be contributed to by the fact that nomograms were not used, INRs were not necessarily checked daily and dosing was based more on individual INR readings without observing INR trends.…”
Section: Resultsmentioning
confidence: 98%
“…During the first week of warfarin initiation, the percentage of INRs of more than 4 were reported as 7% by Roberts et al. (10) and up to 32% by Roberts and Adams (11). The baseline cohort of this study at 27% could be contributed to by the fact that nomograms were not used, INRs were not necessarily checked daily and dosing was based more on individual INR readings without observing INR trends.…”
Section: Resultsmentioning
confidence: 98%
“…The study was designed to detect a change in prescribing practice of 15% (from 50% to 65% appropriate prophylaxis). This estimate of effect was based on two previous studies which had used EOVs to improve VTE prophylaxis in the acute care setting [ 25 , 26 ]. A total sample size of 300 patients (150 pre and 150 post intervention) was necessary to power the study at 80% with a significance level of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…Two more recent studies (9, 10) have used EOVs as a strategy to increase compliance with VTE prevention guidelines among doctors in the hospital setting. Roberts and Adams's study (9) showed an increase of 14.2% (p=0.004) in guideline adherence for medical patients from a baseline of 52.8%. Grupper et al (10) reported a 21% (p<0.001) increase in VTE guideline compliance for surgical patients using EOVs.…”
Section: Introductionmentioning
confidence: 90%